The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1371/journal.pone.0007172
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Re-Entry and Mitochondrial Defects in Myc-Mediated Hypertrophic Cardiomyopathy and Heart Failure

Abstract: While considerable evidence supports the causal relationship between increases in c-Myc (Myc) and cardiomyopathy as a part of a “fetal re-expression” pattern, the functional role of Myc in mechanisms of cardiomyopathy remains unclear. To address this, we developed a bitransgenic mouse that inducibly expresses Myc under the control of the cardiomyocyte-specific MHC promoter. In adult mice the induction of Myc expression in cardiomyocytes in the heart led to the development of severe hypertrophic cardiomyopathy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 40 publications
(57 reference statements)
0
45
0
Order By: Relevance
“…In many instances, persistent cycling of cardiomyocytes has been associated with concurrent apoptosis, defective differentiation, and lethal heart failure; e.g., after combined deletion of Rb plus p130 (MacLellan et al 2005), forced expression of Myc (Lee et al 2009), or combined deletion of miR-133a-1 and miR-133a-2 (Liu et al 2008). This might not be the obligatory consequence of cycling itself, but rather a reflection of specific genes' dual roles in growth and differentiation.…”
Section: The Cardiac Cell Cycle As a Therapeutic Targetmentioning
confidence: 99%
“…In many instances, persistent cycling of cardiomyocytes has been associated with concurrent apoptosis, defective differentiation, and lethal heart failure; e.g., after combined deletion of Rb plus p130 (MacLellan et al 2005), forced expression of Myc (Lee et al 2009), or combined deletion of miR-133a-1 and miR-133a-2 (Liu et al 2008). This might not be the obligatory consequence of cycling itself, but rather a reflection of specific genes' dual roles in growth and differentiation.…”
Section: The Cardiac Cell Cycle As a Therapeutic Targetmentioning
confidence: 99%
“…Results showed that the induction of MYC expression in cardiomyocytes led to the development of severe hypertrophic cardiomyopathy followed by ventricular dysfunction and ultimately death from congestive heart failure. MYC activation in cardiomyocytes is an important regulator of downstream pathological sequelae (Lee et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The Myc network has been studied extensively in cancer cells and may account for the Warburg effect, which fuels the survival and proliferation of cancer cells (46,47,49,50,77,185,215) by activating glycolysis and mitochondrial metabolism. Furthermore, c-Myc also appears to transduce ER-Ca ϩϩ signals (possibly relevant to excitation-contraction coupling in muscle) and affect mitochondrial functions (220) and mitochondrial biogenesis, independent of PGC-1␣, in cardiac muscle (122). Equally relevant to control of glycemia by exercise is the observation that Myc may also transduce insulin signals (193).…”
Section: Interactions Between Signaling Network Modulated By Lactatementioning
confidence: 99%
“…Several genes encoding the glycolytic enzymes have the canonical E-box in their promoters (109). The contribution of the Myc network on the expression of the mitochondrial electron transport chain and mitochondrial biogenesis, possibly independent of PGC-1␣, has been described in the cardiac muscle (1,122). Bioinformatic network analysis of exercise-sensitive transcriptome of human muscles identified Myc to be a "hot spot" that connects changes in multiple transcripts (106).…”
Section: Modulation Of Mitodyn By Second Messenger Networkmentioning
confidence: 99%
See 1 more Smart Citation